1991
DOI: 10.1017/s0890037x00027500
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Weed Management–A Component of Integrated Pest Management: A Critical Review

Abstract: Integrated weed management (IWM) is a component of integrated pest management (IPM), which is an interdisciplinary practice involving disciplines such as entomology, nematology, plant pathology, weed science, horticulture, agronomy, ecology, economics, and systems science. Most descriptions of IPM mention three elements: a) multiple tactics (for example, competitive varieties, cultural practices, herbicide usage) used in a compatible manner; b) pest populations maintained below levels that cause economic damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…In organic agriculture, the use of herbicides is forbidden, therefore, more attention is paid to agrotechnical methods of weed control as well as mechanical, biological and physical ones (Eisele 1998;Hucl 1998;O'Donovan et al 2007). The integrated system of weed control (IWM -Integrated Weed Managenent) combines effective, environmentally safe, and socially acceptable methods in order to maintain the weed population below the economic threshold of harmfulness (Thill 1991;Duer 1996). The integrated system is based on crop rotation, and carefully performed agrotechnical practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In organic agriculture, the use of herbicides is forbidden, therefore, more attention is paid to agrotechnical methods of weed control as well as mechanical, biological and physical ones (Eisele 1998;Hucl 1998;O'Donovan et al 2007). The integrated system of weed control (IWM -Integrated Weed Managenent) combines effective, environmentally safe, and socially acceptable methods in order to maintain the weed population below the economic threshold of harmfulness (Thill 1991;Duer 1996). The integrated system is based on crop rotation, and carefully performed agrotechnical practices.…”
Section: Introductionmentioning
confidence: 99%
“…The Decision Support System (DSS) is a very important element of IWM for plant protection (PC -Plant Protection). The use of the DSS allows for the forecasting of the weed emergence, and the choice of the most effective method of weed control so that excessive use of herbicides can be avoided (Thill et al 1991;Forcella et al 1993;Jensen and Nielsen 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research and effort have gone into measuring the levels of weed infestations that growers should tolerate instead of applying herbicides or other control measures. Many researchers have made recommendations for using weed thresholds as IPM in US agriculture (Shaw, 1982;Thill et al, 1991;Buhler et al, 1992;Hollingsworth, 1994;Buhler, 1996;Cardina et al, 1996;Norris, 1999). Czapar et al (1997) conducted surveys of growers, agricultural chemical dealers, and farm managers/rural appraisers in Illinois to identify limitations to grower acceptance of economic thresholds for IWM, and found that 9% used economic thresholds as a basis for weed control.…”
Section: Use Of Weed Thresholds and Iwmmentioning
confidence: 99%
“…Integrated weed management has been defined as the intégration of effective, environmentally safe, and sociologically acceptable control tactics that reduce weed interférence below the économie injury level (Thill et al 1991). An integrated weed management strategy must be included in ail parts of a crop production System (Swanton and Weise 1991).…”
Section: Nomenclature Of Chemical Names Cited In the Textmentioning
confidence: 99%